META ANALYSIS: EFFECT OF FOOD DIVERSITY, TEA OR COFFEE CONSUMPTION ON ANEMIA IN ADOLESCENT GIRLS: Meta Analisis: Pengaruh Keanekaragaman Pangan dan Konsumsi Teh atau Kopi Terhadap Anemia Pada Remaja Putri - Diastanti, Yunita; Kalsum, Ummi; Guspianto, Guspianto; Noerjoedianto, Dwi (Universitas Airlangga, 2024)
Background: The prevalence of anemia in adolescent girls in the world is 29.60%, and in Indonesia is 32%. A number of primary studies reveal various determinants that contribute to the occurrence of anemia in adolescent girls. Purpose: To analyze the results of primary studies related to consumption patterns (food diversity and tea/coffee consumption) and the occurrence of anemia in adolescent girls. Methods: The research design was a systematic review with meta-analysis. Journal sources from three databases (Google Scholar, Pubmed, and Scopus) using Publish or Perish software with keywords using boolean operators and featured with PRISMA. Inclusion criteria were full text from 2013 to 2022, articles in Indonesian or English language, cross-sectional studies, and the population was adolescent girls, using multiple logistic regression analysis with adjusted odds ratio. The study obtained nine articles from 11,421 articles identified. Data analysis using Rev.Man 5.4. Results: The prevalence of anemia in adolescent girls was 30.83% (95% CI: 15.71-45.95). Food diversity (SMD=1.87; 95% CI=0.88-3.97; P-value=0.10) and tea or coffee consumption (SMD=2.46; 95% CI=1.15-5.27; P-value=0.02) influence the incidence of anemia in adolescent girls. Conclusion: Low food diversity and tea or coffee consumption increase the risk of anemia in adolescent girls. Implementing balanced nutritional guidelines to prevent anemia is recommended.